Consanguinity and genomic sharing in human evolutionary inference - Pemberton, Trevor (Henry Stewart Talks, 2015)
Identity by descent (IBD): mechanism, Identity by descent (IBD): insight into modern humans, Estimating IBD: Wright inbreeding coefficient, Estimating IBD: genomic inbreeding coefficient, Estimating IBD: runs of homozygosity (ROH), Properties of ROH